Poklicna rehabilitacija pri pacientu po zapletih COVID-19 - Železnik, Sandra (Rehabilitacija (Ljubljana), 2021)
A 55-year-old patient with comorbidities was admitted to the Vocational Rehabilitation Centre of the University Rehabilitation Institute in Ljubljana 10 months after SARS CoV-2 infection with complications. Vocational rehabilitation assessment program revealed aggravated symptoms of old brain stroke that had previously been well compensated, derailment of diabetes and further deterioration of cognitive function with pronounced fatigue. It was established that the patient's current rehabilitation potentials do not allow return to work. Prolonged vocational rehabilitation with a gradual return to work was proposed. It will include activities to improve cognitive, motor and process skills and to increase workplace stamina, workload and endurance. This will be followed by a return to the workplace with a gradual increase of time and workloads and with regular progress monitoring. In the event of insufficient work potentials, permanent work accommodations will be defined.
Keywords: complications; COVID-19; interdisciplinarni pristop; interdisciplinary approach; poklicna rehabilitacija; Rehabilitation, Vocational; return to work; vocational rehabilitation; vračanje na delo; zapleti